Mentoring Connections: Implementing a Student–Alumni Mentor Program in Social Work. (3rd July 2019) - Skrzypek, Candra; Diebold, Josal; Kim, Wooksoo; Krause, Denise
ABSTRACT: A student-alumni mentor program that combines aspects of academic and workplace mentoring was developed and implemented in a school of social work. Foundation-year MSW students (mentees) were matched with school of social work alumni (mentors) in a formal mentoring program. This program was developed to address the needs of MSW students, alumni, and the school of social work by providing students with a professional mentor and fostering ongoing connections and opportunities for involvement for alumni. A model for designing, developing, and implementing this program is presented. Benefits of the program for students, mentors, and the school are discussed as well as lessons learned during implementation.